Supply chain inventory model for deteriorating items with maximum lifetime and partial trade credit to credit-risk customers. Issue 1 (2nd January 2017) - Mahata, Gour Chandra; De, Sujit Kumar
Abstract : In supply chain inventory models, it was assumed that the retailers and their customers must pay for the items as soon as the items are received. However, in practice the supplier is usually willing to provide the retailer a full trade credit period for payments and the retailer just offers the partial trade credit period to his/her customers. In addition, many products such as blood for blood banks, pharmaceuticals, fruit, vegetables, volatile liquids and others deteriorate constantly and have their expiration dates. In this paper, we established optimal lot-sizing policies for a retailer who sells a deteriorating item to credit-risk customers by offering partial trade credit to reduce his/her risk. The objective is to maximize the total profit per unit time of the retailer with respect to the optimal purchase quantity during the optimal cycle time. The concavity of the total profit per unit time is demonstrated using inventory parametric values. Sensitivity analysis is carried out to advise the decision maker to keep an eye on critical inventory parameters.